Compressive and Tensile Strength Increment of Concrete Using Recycled Aggregates and Rice Husk Ash - Md. Mia; Kamal Hosen; Kripendra Chakma (Computational Engineering and Physical Modeling)
This study investigates the use of recycled concrete aggregates (RCA) from deconstructed bridges and rice husk ash (RHA) from brick kiln residue in concrete production. By substituting 20% of cement with RHA, the research aimed to enhance sustainability and concrete performance. Concrete mixtures, using a 1:2:4 ratio for aggregates, sand, and cement, and a 0.46 water/cement ratio, were tested for compressive and tensile strengths at 14 and 28 days. The results showed substantial improvements, with a 4.75% increase in compressive strength and an 8.05% increase in tensile strength for concrete incorporating 20% RHA and 100% RCA after 28 days. This study highlights the potential of RCA and RHA to produce more sustainable, high-performance concrete. It emphasizes the practicality and benefits of integrating RCA and RHA, suggesting this approach could significantly contribute to environmentally friendly construction practices. The research also underscores the necessity for further studies to optimize the ratios and techniques for incorporating RCA and RHA, fully harnessing their benefits in concrete applications.